145k views
3 votes
The function h(x)= x^2+3 and g(x)= x^2-6. if g(x) = h(x) +k, what is the value of k

The function h(x)= x^2+3 and g(x)= x^2-6. if g(x) = h(x) +k, what is the value of-example-1
User Kiefer
by
5.5k points

1 Answer

6 votes

ANSWER


k = - 9

Step-by-step explanation

The given functions are:


h(x) = {x}^(2) + 3

and


g(x) = {x}^(2) - 6

We want to find the value of k, if

g(x)=h(x)+k

We need to rewrite g(x) in terms of h(x)


{x}^(2) - 6 = {x}^(2) + 3 - 9

Thus,

g(x)=h(x)+-9

This implies that

k=-9

User Thomas Ducrot
by
5.1k points